ORGANIC FARMING: TOWARDS SUSTAINABLE AGRICULTURE - Mukesh Kr. Meena, Dr. Sonlata Bargotya, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Organic farming, also known as ecological farming or biological farming, is an agricultural system that uses fertilizers of organic origin such as compost manure, green manure, and bone meal and places emphasis on techniques such as crop rotation and companion planting. Organic farming can be defined as an agricultural process that uses biological fertilizers and pest control acquired from animal or plant waste. Organic farming was actually initiated as an answer to the environmental sufferings caused by the use of chemical pesticides and synthetic fertilizers. In other words, organic farming is a new system of farming or agriculture that repairs, maintains, and improves the ecological balance.